Voltage and frequency control strategies of hybrid AC/DC microgrid: a review. Issue 2 (1st January 2017) - Malik, Sarmad Majeed; Ai, Xin; Sun, Yingyun; Zhengqi, Chen; Shupeng, Zhou
Abstract : Microgrids have become an attractive option for distributed generation (DG) with increase in renewable energy sources (RES) and storage systems. The existence of both AC and DC microgrids has led to a new concept of hybrid AC/DC microgrid which consists of both AC and DC grids tied by an interlinking converter (ILC). Such hybrid AC/DC microgrid has the advantages of both AC and DC with increased efficiency and less cost since the conversion between AC and DC is reduced. The management of power in such a grid becomes important for voltage and frequency control. Different voltage and frequency control strategies have been successfully implemented within AC and DC grids, but the control of hybrid microgrid requires further attention with focus on ILC. This study presents an overview of various control schemes used for voltage and frequency regulation in standalone and transition mode operation of hybrid microgrid. A detailed study on hybrid grid structure is presented with different modes of operation. Various ILC strategies based on droop and communication‐based control are presented. Based on the analysis, some recommendations are presented for future research.